Hyperelodiones A-C, monoterpenoid polyprenylated acylphoroglucinols from Hypericum elodeoides, induce cancer cells apoptosis by targeting RXRα. (February 2020) - Qiu, Daren; Zhou, Mi; Chen, Junjie; Wang, Guanghui; Lin, Ting; Huang, Yujie; Yu, Furong; Ding, Rong; Sun, Cuiling; Tian, Wenjing; Chen, Haifeng
Abstract: Hyperelodiones A-C, three undescribed monoterpenoid polyprenylated acylphloroglucinols possessing 6/6/6 fused tricyclic core, were isolated from Hypericum elodeoides Choisy. Their gross structures were elucidated by HRESIMS and NMR data. The absolute configurations of hyperelodiones A-C were assigned by their calculated and compared electronic circular dichroism (ECD) spectra combined with their common biosynthetic origin. A fluorescence quenching assay suggested that hyperelodiones A-C could bind to RXRα-LBD, whereas hyperelodione C showed the strongest interaction with a KD of 12.81 μΜ. In addition, hyperelodiones A-C dose-dependently inhibited RXRα transactivation and the growth of HeLa and MCF-7 cells. Among them, hyperelodione C showed the most potent inhibitory activities and dose-dependent PARP cleavage. Molecular docking results suggested that hyperelodione C showed a different interaction mode compared with hyperelodione A and hyperelodione B. Thus, hyperelodione C can be considered as a promising lead compound for cancer therapy, which can bind to RXRα-LBD and induce HeLa and MCF-7 cell apoptosis. Graphical abstract: Hyperelodione C from the plant of Hypericum elodeoides Choisy induce cancer cell apoptosis by targeting RXRα-LBD. Image 1 Highlights: Three monoterpenoid polyprenylated acylphloroglucinols from Hypericum elodeoides. The isolated compounds could induce cancer cell apoptosis. The isolated compounds could bind to RXRα-LBD. The isolated compounds could inhibit RXRα transactivation.